1984
DOI: 10.1139/v84-032
|View full text |Cite
|
Sign up to set email alerts
|

The hydration parameter and the excess acidity functions in H2SO4–H2O and HClO4–H2O media

Abstract: PIETRO GIUSEPPE TRAVERSO. Can. J. Chem. 62, 153 ( 1984). Excess acidities, X, for aqueous H'SO, and HCIO, arc derived under conditions of fixed pKBbI+ and 111:' : in both media. and of fixed m* only, and compared among themselves and with newly derived and previous scales obtained without constraint, or with fixed pK,,+ valucs. Analysis shows few or no real diffcrcnces among these scalcs. which means that the equation log I + log C,,+ = pK,H+ + nl:':X applies without the necessity of involving a "second-order"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The structural modification of water has been investigated conductometrically for perchlorates in methanol solution 12 . In aqueous solution the hydration studies have been reported 13,14 . In the present study the viscometric studies of aqueous concentrated perchloric acid have been undertaken in order to obtain interaction parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The structural modification of water has been investigated conductometrically for perchlorates in methanol solution 12 . In aqueous solution the hydration studies have been reported 13,14 . In the present study the viscometric studies of aqueous concentrated perchloric acid have been undertaken in order to obtain interaction parameters.…”
Section: Introductionmentioning
confidence: 99%